The Role of Investment, Infrastructure, Migration of Employment Opportunities; Study Literature Review - Rustam Rustam; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (Cita konsultindo, 2023)
Labor problems are not only micro-scale problems but have macro-scale coverage. Because labor problems if not touched with the right policy will lead to conflict: both horizontal conflict and vertical conflict. High unemployment rates can create problems at the social and economic levels. So this research aims to examine how the role of investment variables, and other control variables in providing influence on employment opportunities aimed at community welfare. The methodology/approach in this research uses a descriptive approach, which is focused on secondary data sources. Secondary data is collected through books, newspapers, journals, articles, and government websites. The results show that the variables that affect the level of community welfare through employment opportunities are economic growth, investment, infrastructure, education, migration. In particular, in increasing employment opportunities, the government has an important role in opening policy taps that are able to improve the welfare of its people through employment opportunities. Meanwhile, wages have a negative relationship in influencing employment opportunities.